2020
DOI: 10.35118/apjmbb.2020.028.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of Pennisetum purpureum for phytoremediation and bioenergy production: a mini review

Abstract: Organic and/or heavy metal pollutants in soil and wastewater can be remediated by phytoremediation. Phytoremediation combines the disciplines of plant physiology, soil microbiology and soil chemistry. There are several ways by which plants extract, stabilize, filtrate, volatilize or degrade the contaminants. However, the effectiveness of phytoremediation relies upon the type of plant used. Pennisetum purpureum, commonly referred to as Napier grass, is one of the exceptional phytoremediators due to its rapid gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…Cỏ voi sinh trưởng nhanh, cho sinh khối cao, chống chịu tốt các điều kiện môi trường, và có khả năng hấp thu kim loại nặng (Qin et al, 2022). Các nghiên cứu trước đây đã sử dụng cỏ voi để xử lý nước thải chăn nuôi heo (Pantip, 2016), nước thải nhà máy dầu (Osman et al, 2020) và nước thải sinh hoạt (Xu et al, 2015) trong hệ thống ĐNN. Cỏ voi có thể hấp thu rất tốt đối với cả nitrogenvà phosphate trong nước thải sinh hoạt (Xu et al, 2015).…”
Section: Giới Thiệuunclassified
“…Cỏ voi sinh trưởng nhanh, cho sinh khối cao, chống chịu tốt các điều kiện môi trường, và có khả năng hấp thu kim loại nặng (Qin et al, 2022). Các nghiên cứu trước đây đã sử dụng cỏ voi để xử lý nước thải chăn nuôi heo (Pantip, 2016), nước thải nhà máy dầu (Osman et al, 2020) và nước thải sinh hoạt (Xu et al, 2015) trong hệ thống ĐNN. Cỏ voi có thể hấp thu rất tốt đối với cả nitrogenvà phosphate trong nước thải sinh hoạt (Xu et al, 2015).…”
Section: Giới Thiệuunclassified
“…The outcome of the study indicated that hemp growth has been successfully proved at the field scale for phytoremediation and in key bioenergy conversion technologies. Additionally, Osman et al [22] investigated the potential of employing Pennisetum purpureum for phytoremediation and bioenergy production. The study revealed that P. purpureum contains high levels of lignocellulosic content, which can be used as a carbon source for the production of bioenergy like ethanol and butanol.…”
Section: Integration Of Phytoremediation With Bioenergy Productionmentioning
confidence: 99%
“…Napier grass is mainly cultivated as a forage crop for animal feed due to its high palatability and feed quality, high dry matter production (up to 78 tons of dry matter/ha/year), and year-round availability under supplementary irrigation 1 , 5 7 . In addition, Napier grass has the potential to produce biofuels such as alcohol, ethanol and butanol, and methane since it has high cellulose content that can be used as a carbon (energy) source 8 11 . It has many other beneficial characteristics, including resistance to most pests and diseases, ease of establishment and fast regrowth capacity, withstanding repeated cuttings.…”
Section: Introductionmentioning
confidence: 99%